Co-targeting B-RAF and PTEN Enables Sensory Axons to Regenerate Across and Beyond the Spinal Cord Injury - Noristani, Harun N.; Kim, Hyukmin; Pang, Shuhuan; Zhong, Jian; Son, Young-Jin (Frontiers in Molecular Neuroscience, 2022)
Primary sensory axons in adult mammals fail to regenerate after spinal cord injury (SCI), in part due to insufficient intrinsic growth potential. Robustly boosting their growth potential continues to be a challenge. Previously, we showed that constitutive activation of B-RAF (rapidly accelerated fibrosarcoma kinase) markedly promotes axon regeneration after dorsal root and optic nerve injuries. The regrowth is further augmented by supplemental deletion of PTEN (phosphatase and tensin homolog). Here, we examined whether concurrent B-RAF activation and PTEN deletion promotes dorsal column axon regeneration after SCI. Remarkably, genetically targeting B-RAF and PTEN selectively in DRG neurons of adult mice enables many DC axons to enter, cross, and grow beyond the lesion site after SCI; some axons reach ~2 mm rostral to the lesion by 3 weeks post-injury. Co-targeting B-RAF and PTEN promotes more robust DC regeneration than a pre-conditioning lesion, which additively enhances the regeneration triggered by B-RAF/PTEN. We also found that post-injury targeting of B-RAF and PTEN enhances DC axon regeneration. These results demonstrate that co-targeting B-RAF and PTEN effectively enhances the intrinsic growth potential of DC axons after SCI and therefore may help to develop a novel strategy to promote robust long-distance regeneration of primary sensory axons.